The concept of Miraculousness among orientalists - AlIbrahimi, Karar Abdul-Ilah Abdul-Kazim (Thi Qar Arts Journal, 2022)
This study stands on an issue that preoccupied the Islamic world, and the Western world before it, which is the position of the orientalists towards the Holy Qur’an, from many aspects. The scientific methodology called for this study to be divided into an introduction, two chapters and a conclusion. In the preamble, we stand on the emergence of the subject of the miraculousness of the orientalists, while we study in the first section the purpose of the miraculousness, and the concept of orientalism, and then we study in the second section the motives of the Holy Quran by the orientalists and their position on it.